Microstructure and mechanical properties of titanium-containing steel weld metal with varying molybdenum and nickel levels before and after thermal cycling - Pistorius, P.G.H. (Pieter) (University of Pretoria, 2022)
Thesis (PhD (Metallurgy))--University of Pretoria, 2021.